Triaxial residual strains in a railway rail measured by neutron diffraction - Jun, T; Hofmann, F; Belnoue, J; Song, X; Hofmann, M; Korsunsky, A (Professional Engineering Publishing, 2009)
Accumulation of residual stresses in rails during service can contribute to crack initiation and fracture and may result in serious accidents. It is therefore necessary and important to quantify the residual stresses that evolve under repeated rolling contact between wheel and rail. In the present study, triaxial residual strain measurements were performed in a worn British railway rail using neutron diffraction. Localized stress is observed close to the region of contact, showing the asymmetry and complexity of distributions that arise from the non-uniform plastic deformation. Contact-induced plasticity is revealed by the broadening (increase in the full width at half-maximum (FWHM)) of the diffraction peaks. © IMechE 2009.